Do obstetric units adhere to the evidence-based national guideline? A Germany-wide survey on the current practice of initial tocolysis. (March 2022) - Stelzl, Patrick; Kehl, Sven; Oppelt, Peter; Maul, Holger; Enengl, Sabine; Kyvernitakis, Ioannis; Rath, Werner
Highlights: Tocolysis should be applied by 48 h to complete fetal lung maturation. "Patient's fear" to deliver preterm leads to "polypragmasia" regarding. tocolysis. Experience of severe side effects influences obstetrician's decision for or against tocolysis. National surveys after implementation of guidelines improve obstetric health care. Abstract: Objectives: Current international guidelines recommend tocolytic treatment by at least 48 h to complete fetal lung maturation and to ensure in-utero transfer to a perinatal center before 34 weeks of gestation in patients with threatened preterm birth. According to the results of former surveys, significant differences between daily clinical practice patterns and evidence-based guideline recommendations regarding tocolytic treatment have been demonstrated. We compared data from a nation-wide survey on the practice of initial tocolysis with recommendations from the current German Guideline 015/025 "Prevention and Treatment of Preterm Birth". Study design: 632 obstetric units in Germany received a link to an online questionnaire between January 20th and March 31st 2020, which was developed according to national and international recommendations and guidelines. Collected data was descriptively analyzed by performing measures of frequency. Results: The response rate was 19%; 51 (42.5%) of the respondents consider CTG tracing with ≥ 4 contractions within 20 min, 49 (40.8%) cervical length measurement of ≤ 25 mm and 13 (10.9%) subjective contractions as the most significant decision-making criteria for tocolysis; 47 (39.2%) of obstetric units initiate tocolysis earliest at 23 + 0, 34 (28.3%) at 22 + 0, 26 (21.7%) at 23 + 5 and 13 (10.8%) at 24 + 0 weeks of gestation; 104 (86.7%) stop tocolysis latest at the 34 + 0 weeks of gestation, 42 (35.0%) obstetric units administer antenatal corticosteroids at 23 + 5, 16 (13.3%) at 22 + 0, and 13 (10.8%) at 24 + 0 weeks of gestation. Calcium channel blockers are the first-line tocolytic drug used by 59 (49.1%) of the obstetric units, followed by intravenous betamimetics as bolus (n = 26, 21.7%) and atosiban (n = 20, 16.7%). Severe side-effects were observed by 105 (70%) of the respondents in association with the use of betamimetics, 14 (9.3%) with the use of nifedipine and 30 (20.0%) with nitroglycerine patches. The German guideline was considered the most important decision-making support by 78 (65%) of the obstetric units, followed by hospital specific SOPs/algorithms (n = 31, 25.8%). Conclusion: Our survey highlights a considerable discrepancy between evidence-based guideline recommendations and daily clinical practice.